Urban and rural variation in walking patterns and pedestrian crashes. Issue 6 (11th December 2008) - Zhu, M; Cummings, P; Chu, H; Xiang, H
Abstract : Objective: To examine the urban and rural variation in walking patterns and pedestrian crashes. Design: The rates of pedestrians being struck by motor vehicles was estimated according to miles walked and resident years. Setting: New York State, USA during 2001 through 2002. Participants: 35 732 pedestrians struck by vehicles. Main outcome measures: The adjusted rate ratio (aRR) of pedestrian–vehicle crash and pedestrian injury based on resident years and miles walked according to urban and rural areas. Results: Compared with rural areas, the aRR for a pedestrian–vehicle collision, based on resident years, was 2.0 (95% CI 1.7 to 2.3) in small urban areas, 1.8 (95% CI 1.5 to 2.3) in mid-size urban areas, and 4.2 (95% CI 3.6 to 4.8) in the large urban area. The aRR based on miles walked was 2.3 (95% CI 1.6 to 3.2) in small urban areas, 2.0 (95% CI 1.4 to 2.9) in mid-size urban areas, and 1.9 (95% CI 1.4 to 2.7) in the large area. The aRR for a fatal pedestrian injury, based on miles walked, was 2.1 (95% CI 1.3 to 3.6) in small urban areas, 1.9 (95% CI 1.3 to 2.9) in mid-size urban areas, and 0.9 (95% CI 0.6 to 1.3) in the large urban area. Conclusions: The rate of pedestrian crashes and injuries in small and mid-size urban areas was twice that in rural areas, whether based on resident years or miles walked. The high rate of pedestrian crashes in the large urban area based on resident years could be partly explained by the fact that residents in such areas walk about twice as much as residents in rural areas. The rate of fatal pedestrian injury based on miles walked was similar in the large urban area and rural areas.